AN ANALYSIS OF STUDENTS’ ABILITY IN UNDERSTANDING ENGLISH POETRY AT THE THIRD GRADE OF ENGLISH STUDY PROGRAM STATE POLYTECHNIC OF BENGKALIS - Fanalisa Elfa; Arita Destianingsih; Ari Satria (INOVISH JOURNAL, 2019)
This research aims to analyse the ability of students’ ability in understanding English poetry at the third grade of English Study Program, State polytechnic of Bengkalis. The type of the research was descriptive research. The data of the research were collected by administering written English Poetry test. The finding shows that the average score of ability of the students in understanding English poetry is poor. The categories of students’ ability were; sound categorized poor, structure categorized poor, and sense categorized poor. It means that the students’ ability in understanding English poetry was poor.